Meta-analysis of the effects of denosumab and romosozumab on bone mineral density and turnover markers in patients with osteoporosis - Hu, Mingwei; Zhang, Yifan; Guo, Jianjun; Guo, Cuicui; Yang, Xue; Ma, Xue; Xu, Hao; Xiang, Shuai (Frontiers in Endocrinology, 2023)
Purpose To assess the alterations in bone mineral density and bone turnover marker concentrations following the administration of denosumab and romosozumab therapies in patients with osteoporosis. Methods PubMed was searched for studies published until January 28, 2023, that investigated the clinical efficacy and bone turnover marker changes of denosumab and romosozumab in the treatment of osteoporosis, with a minimum follow-up of 3 months in each study. Studies were screened, and data on changes in bone mineral density (BMD), P1NP, and TRACP-5b levels after treatment were extracted and included in the analysis. Results Six studies were analyzed. At 3 months after treatment, the romosozumab group showed greater changes in lumbar BMD and bone turnover markers. BMD of total hip and femoral neck was relatively delayed. Beginning at 6 to 12 months, romosozumab showed greater changes in bone mineral density and markers of bone turnover. Conclusion Both romosozumab and denosumab have antiosteoporotic effects, with greater effects on BMD and bone turnover markers observed within 12 months of romosozumab treatment. Systematic Review Registration https://www.crd.york.ac.uk/prospero, identifier CRD42023395034.